Memahami Hubungan Simbol Keseimbangan Gender dalam Rumah Adat dan Tindakan Masyarakat - Ziel Elizabeth Limahelu; Izak Yohan Matriks Lattu; Ebenhaizer Imanuel Nuban Timo (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2019)
Symbols can be used to give meaning to social behavior, especially in explaining the meaning of the symbol of the equality of life of a cultural community. This study aims to describe and analyze the symbolization and meaning of gender equality from the traditional culture house of the Umametan Lawalu community in Belu NTT. A descriptive qualitative study with a narrative approach was carried out through in-depth interview techniques and field observations, then the data were analyzed using interpretative techniques. This study results in the finding that the traditional house does not only function as a place to live but as a cultural identity that is a condition with a symbol of social behavior. The symbol of equality can be shown from the great pillar found in the Umametan Lawalu traditional house in Belu NTT. Symbols at the poles teach people that women and men have the same role in the social and cultural public sphere, the relationship between men and women becomes an amplifier of social action with each other.